Sustainable Energy in Chile; Present and Future Prospect for Wave Power. - Saenz, Fernando (2006)
Growing concern for greenhouse emissions, energy diversification and self-autonomy of energy sources has placed particular importance on renewable energies not only in developed economies but also in developing economies. Chile is currently suffering an energy problem and renewable energies are an ideal solution to this problem.